ROMANIAN LANGUAGE AND LITERATURE: INTERCULTURAL EDUCATION IMPLICATIONS - GORAS-POSTICA, VIORICA (Society Register, 2019)
The study approaches the new curriculum documents for pre-university education in the Republic of Moldova from the intercultural education perspective. In the 2019-2020 school year, the schools in the country are carrying out the education process based on a new curriculum, which represents the result of the third reform after the country's independence in 1992. The author analyses the correspondence of the curriculum texts to the stipulations of the Education Code, and the extent to which they respond to the demands in the development of the students’ intercultural competence. The findings of the study reveal that the texts are focused not only on the promotion of the national values and identity, but are open, at the same time, to the intercultural education and to the dialogue with representatives of different cultures in the multicultural divided society. Literature and policy review supplemented by discourse analysis are the main qualitative methods applied.